MUNICIPAL SOLID WET WASTE MANAGEMENT BY PUBLIC PARTICIPATION - Jain, Shailendra; Jain, Manjula (International Journal of Research -GRANTHAALAYAH, 2015)
The municipal solid wet waste is an organic fraction that contributes to around 40% of total waste and it is biodegradable. In the present scenario, wet waste is generally mixed with other kinds of waste that is not bio-degradable. The foul smell is generated from the wet waste if not disposed within 24 hrs. This smell creates problem for people exposed to handling and management system. All biological treatment technologies applied to the wet (organic) waste treatment would require segregation of biodegradable and non-bio-degradable components. Once the waste of different categories is mixed it becomes very difficult to segregate them effectively. Many large size plants in the country are constructed to treat biodegradable waste with the objective to recover energy and produce organic manure but its smooth operation faces great challenge of accurate segregation resulting into plant break down and failures irrespective of robust technology. This research paper focuses on unique approach of public participation for segregation at source by deploying micro level biological treatment plants of capacity ranging from 1.0 MT/d to 5 MT/d. With the implementation of above approach and treatment technology, huge efforts that are presently put to segregate the waste will be eliminated. In addition to this, the energy and organic manure as end product obtained from the treatment plant makes it as self-sustainable.